1991
DOI: 10.1001/archpsyc.1991.01810340060008
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorders in Children and Their Families

Abstract: Probands included 94 children with an anxiety disorder, 58 children with ADHD, and 87 NPI children. Probands with anx¬ iety disorder were recruited from the Child and Adolescent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
0
7

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(169 citation statements)
references
References 24 publications
12
150
0
7
Order By: Relevance
“…Recently, children with ADHD were found to develop new anxiety disorders at a comparable rate to a sample of DSM-IIIR anxiety-disordered children (Last, Perrin, Hersen, & Kazdin, 1992), and to have high rates of co-morbid anxiety (Anderson, Williams, McGee, & Silva, 1987;McClellan, Rubert, Reichler, & Sylvester, 1990) and anxiety in their firstdegree relatives (Biederman, Faraone, Keenan, Knee, & Tsuang, 1990;Last, Hersen, Kazdin, Orvaschel, & Perrin, 1991). McClellan et al (1990) found an increased rate of ADHD in the offspring of panic disordered adults vs. depressed and normal adults.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, children with ADHD were found to develop new anxiety disorders at a comparable rate to a sample of DSM-IIIR anxiety-disordered children (Last, Perrin, Hersen, & Kazdin, 1992), and to have high rates of co-morbid anxiety (Anderson, Williams, McGee, & Silva, 1987;McClellan, Rubert, Reichler, & Sylvester, 1990) and anxiety in their firstdegree relatives (Biederman, Faraone, Keenan, Knee, & Tsuang, 1990;Last, Hersen, Kazdin, Orvaschel, & Perrin, 1991). McClellan et al (1990) found an increased rate of ADHD in the offspring of panic disordered adults vs. depressed and normal adults.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although the diagnostic methods for anxiety disorders in children are similar to those used in adults, the assessment and treatment of pathological anxiety in children have peculiar characteristics.…”
Section: Clinical Course and Treatmentmentioning
confidence: 99%
“…Studies of the offspring of anxiety-disordered (AD) adults have demonstrated that these children are at high risk of becoming anxietydisordered themselves [1][2][3][4]. Likewise, parents and siblings of AD children show a higher prevalence of anxiety disorders than is found in general [5,6] Behavioural-genetic research has demonstrated that heredity accounts for part of the familial transmission of anxiety disorders, but it has indicated a substantial environmental contribution as well [7][8][9].…”
Section: Introductionmentioning
confidence: 99%